2018
DOI: 10.1186/s40942-018-0129-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute retinal vein occlusion and cystic fibrosis

Abstract: BackgroundThe ocular manifestations of cystic fibrosis typically present with surface irritation or nyctalopia due to Vitamin A deficiency, however, there have been two previous reports of patients with cystic fibrosis that developed retinal vein occlusions. These reports hypothesized that either elevated fibrinogen levels due to chronic infections or elevated homocysteine levels have predisposed patients with cystic fibrosis to develop retinal vein occlusions.Case presentationWe present a case of a 35-year-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“… Note : Data from these studies 15 , 19 , 20 , 23 , 30 , 36–39 , 41 , 42 , 47 , 61 , 62 . Abbreviations : CF, cystic fibrosis; CFTR-RD, cystic fibrosis transmembrane conductance regulator-related disorder; DED, dry eye disease; pRNFL, peripapillary retinal nerve fiber layer; SPEED, Standard Patient Evaluation of Eye Dryness; OSDI, Ocular Surface Disease Index; TBUT, tear break-up time; MMP-9, matrix metalloproteinase-9; ELISA, enzyme-linked immunosorbent assay; IL-8, interleukin-8; IFN-γ, interferon-γ; MIP-1α, macrophage inflammatory protein-1α; MIP-1β, macrophage inflammatory protein-1β.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Note : Data from these studies 15 , 19 , 20 , 23 , 30 , 36–39 , 41 , 42 , 47 , 61 , 62 . Abbreviations : CF, cystic fibrosis; CFTR-RD, cystic fibrosis transmembrane conductance regulator-related disorder; DED, dry eye disease; pRNFL, peripapillary retinal nerve fiber layer; SPEED, Standard Patient Evaluation of Eye Dryness; OSDI, Ocular Surface Disease Index; TBUT, tear break-up time; MMP-9, matrix metalloproteinase-9; ELISA, enzyme-linked immunosorbent assay; IL-8, interleukin-8; IFN-γ, interferon-γ; MIP-1α, macrophage inflammatory protein-1α; MIP-1β, macrophage inflammatory protein-1β.…”
Section: Discussionmentioning
confidence: 99%
“…[50][51][52][53][54][55][56] AMEED and Regener-Eyes ® are not currently FDA approved but have promising therapeutic potential as they leverage their anti-inflammatory, anti-angiogenic, and nonimmunogenic properties to promote limbal stem cell proliferation, facilitate corneal epithelial healing, and treat DED. [54][55][56] Note: Data from these studies 15,19,20,23,30,[36][37][38][39]41,42,47,61,62…”
mentioning
confidence: 99%
“…The most common vascular changes were venous engorgement, tortuosity, and dilatation—at least one of them was seen in 20/23 patients, while retinal hemorrhages were found in 9 patients [ 77 ]. The case report of branch retinal vein occlusion (BRVO) with secondary macular edema in a 35-year-old male CF patient with elevated serum fibrinogen levels was described by Starr et al [ 92 ]. Hiscox et al described a similar case of a 35-year-old male CF patient with BRVO and hyperfibrinogenemia [ 93 ].…”
Section: Changes Of the Retinal And Choroidal Vasculaturementioning
confidence: 99%
“…Night blindness is the first sign of vitamin A deficiency with further symptoms after prolonged periods of deficiency, such as Bitot’s spots; triangular, perilimbal grey plaques of keratinized conjunctival debris; and xerosis and dry granular patches. Furthermore, patients with CF have been reported to develop retinal vein occlusions [ 20 , 53 , 54 ]. It has been hypothesized that elevated fibrinogen levels due to chronic infections or increased homocysteine levels predispose patients with CF to develop retinal vein occlusions.…”
Section: Ocular Disorders Derived From Cystic Fibrosis Diseasementioning
confidence: 99%
“…Another clinical study carried out by Seliger et al demonstrated that 91.1% of CF patients were diagnosed with cataract disease [ 18 ], which is in line with another clinical study conducted in the US evaluating the risk of cataracts of pediatric patients with cystic fibrosis [ 19 ]. More aggressive ocular problems were described by Starr et al in a 35-year-old male with CF that presented intraretinal hemorrhages along the nerve fiber layer with associated retinal thickening in the inferior macula, which means an acute branch retinal vein occlusion in his left eye with associated macular edema [ 20 ]. Rottner et al showed that CF patients are at high risk of developing retinal vein occlusions due to several systemic thrombogenic factors, such as diabetes, hypertension, hyperlipidemia, an elevated level of fibrinogen, hyperhomocysteinemia, or hypergammaglobulinemia [ 21 ].…”
Section: Introductionmentioning
confidence: 99%